Analysis of Tractor-Associated Fatalities - Turkoglu, Abdurrahim; Sehlikoglu, Kerem; Tokdemir, Mehmet (Lippincott Williams & Wilkins, 2017)
Introduction and Objective Tractor is regarded as a key equipment in agriculture, and it is also used for transportation and transfer purposes in addition to its agricultural use. Accidents resulting in death in farmlands are frequently encountered. Tractor-related fatalities are the most common ones among the deaths after farm accidents. This study aimed to evaluate the characteristics of tractor-related deaths and to discuss the measures that could be taken to prevent these deaths. Methods In this study, 42 cases who underwent postmortem examination and/or autopsy because of tractor fatalities in the province of Elazig between January 2005 and December 2016 were examined retrospectively with such variables as sex, age, month and season of incident, cause of incident, location of incident, position of case, and injured region. Results Of the cases, 36 (85.7%) were male, and 6 (14.3%) were female. The youngest case was 2 years old, and the oldest case was 83 years old; the mean age was 43.3 25.0 years. Examining the deaths regarding the cause of incident showed that tractor rollover was the most common cause (42.9%). This was followed by being run over by the tractor (19.0%). Of the cases, 24 (57.1%) were drivers, 10 (23.8%) were passengers, and 8 (19.0%) were pedestrians. Conclusions Tractor-related fatalities due to tractor rollover are most often seen. To reduce the deaths caused by this reason, drivers should have special training and technical support, use helmets and seatbelts in the tractor, and have a health check at certain intervals (especially the drivers at advanced age).
Keywords: accident; agriculture; autopsy; rollover; tractor